Bringing Secrecy into the Open: Towards a Theorization of the Social Processes of Organizational Secrecy. Issue 10 (October 2014) - Costas, Jana; Grey, Christopher
This paper brings into focus the concept of organizational secrecy, defined as the ongoing formal and informal social processes of intentional concealment of information from actors by actors in organizations. It is argued that existing literature on the topic is fragmented and predominantly focused on informational rather than social aspects of secrecy. The paper distinguishes between formal and informal secrecy and theorizes the social processes of these in terms of identity and control. It is proposed that organizational secrecy be added to the analytical repertoire of organization studies.